RETRACTED: Market-financial mechanisms of institutional support for the economic development of the Republic of Crimea - Kirilchuk Svetlana; Nalivaychenko Ekaterina; Kirsenko Vladislav (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001